Thermal expansion measurements in the relaxor ferroelectric PIN-PT system - Supattra Wongsaenmai (2018)
Thermal expansion was measured for the ceramic compositions (1 - x)Pb(In0.5Nb0.5)O3-(x)PbTiO3(x = 0.0, 0.1, 0.2 and 0.3) prepared via the wolframite method. The deviation from the straight line below Burns temperature for all the compositions was due to the dynamic polarization fluctuations. Burns temperature was determined and found to increase with increasing PT concentration. The local polarization was calculated from the thermal expansion data. The calculated local polarization and the measured reversible spontaneous polarization were compared and the relaxor behavior of the PIN-PT compositions was analyzed. © 2007 Elsevier B.V. All rights reserved.